2020
DOI: 10.12688/f1000research.22600.1
|View full text |Cite
|
Sign up to set email alerts
|

Causality assessment of adverse events following immunization: the problem of multifactorial pathology

Abstract: The analysis of Adverse Events Following Immunization (AEFI) is important in a balanced epidemiological evaluation of vaccines and in the issues related to national vaccine injury compensation programs. If manufacturing defects or vaccine storage and delivering errors are excluded, the majority of adverse reactions to vaccines occur as excessive or biased inflammatory and immune responses. These unwanted phenomena, occasionally severe, are associated with many different endogenous and exogenous factors, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 178 publications
0
10
0
Order By: Relevance
“…As suggested by World Health Organization (WHO) guidance [ 17 ], Adverse Events Following Immunization (AEFI) represent untoward medical events following vaccination. According to WHO, vaccines could represent the primary factor linked to AEFI or cofactors within complex events [ 18 ], although this approach has shortcomings, but robust alternatives are lacking [ 19 ]. After validating myositis diagnosis and excluding non-vaccination-related causes, biological plausibility and temporal compatibility between the immunization and the occurrence of the AEFIs were assessed as previously described [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by World Health Organization (WHO) guidance [ 17 ], Adverse Events Following Immunization (AEFI) represent untoward medical events following vaccination. According to WHO, vaccines could represent the primary factor linked to AEFI or cofactors within complex events [ 18 ], although this approach has shortcomings, but robust alternatives are lacking [ 19 ]. After validating myositis diagnosis and excluding non-vaccination-related causes, biological plausibility and temporal compatibility between the immunization and the occurrence of the AEFIs were assessed as previously described [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found no evidence of an association between KD and PCV13, PCV 7, or 4CMenB vaccines [17]. However, the vaccine can act as a factor or cofactor with underlying predisposing conditions related to the biological or genetic makeup of the individual and the interaction of multifactorial environmental variables [18]. SARS-CoV-2 infection is known to exacerbate known rheumatologic disease, unmask previously undiagnosed rheumatic conditions, and precipitate de novo disease, which may persist after resolution of the infection.…”
Section: Discussionmentioning
confidence: 98%
“…The difficulty of identifying vaccine-related adverse reactions lies in judging the correlation between the vaccine and the events. 11 At the court’s request, all 14 adverse event reports were reviewed by a panel of five senior clinical experts to assess the causal relationship between adverse events and BCG vaccination. The committee determined that 7 cases had a possible cause-and-effect relationship with the vaccine, including 3 lymphadenitis, 1 disseminated BCGs, 1 myocarditis, and 1 epilepsy ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%